The Idea of Spatiality in Adele: A Feminist Geography Approach - Maabich, Omar (Technium Education and Humanities, 2024)
Feminism is a multidisciplinary field that addresses women’s issues and interests. The field has extended its focus to cover major aspects of women’s lives rising from society, economy, culture, and politics to geography. Feminist geography examines women’s status, interaction, and significance in a place and space. Leila Slimani’s Adele (2019) is a masterpiece that presents a genuine mode of spatiality where the interconnectedness and interplay between the physical and the digital space navigates gender-related issues. This present article addresses the idea of spatiality in Adele, and how the interconnectedness between the physical, and the digital spaces provides a holistic feminist geographical lens to discuss gender roles, inequality, and social discrimination. The study portrays how the protagonist navigates between the two realms effortlessly while exploring how places and spaces are social and gendered constructions. Initially, the digital place helped Adele to escape from the domestics, the family, and the public space, but digital escapism collapsed as it gave more intricate and complexity to the multithemed feminist issues and mode of spatiality in the narrative. Keywords. Domestic place, digital space, feminist geography, gender roles, interconnectedness, interplay, mode of spatiality, space.